2019
DOI: 10.1002/nbm.4215
|View full text |Cite
|
Sign up to set email alerts
|

Detecting liver fibrosis using a machine learning‐based approach to the quantification of the heart‐induced deformation in tagged MR images

Abstract: Liver disease causes millions of deaths per year worldwide, and approximately half of these cases are due to cirrhosis, which is an advanced stage of liver fibrosis that can be accompanied by liver failure and portal hypertension. Early detection of liver fibrosis helps in improving its treatment and prevents its progression to cirrhosis. In this work, we present a novel noninvasive method to detect liver fibrosis from tagged MRI images using a machine learning‐based approach. Specifically, coronal and sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…For example, ultrasound-based MLA is more accurate in detecting steatosis, hepatic fibrosis, and localized liver lesions [9][10][11]. Several studies have demonstrated the efficiency of support vector machine (SVM) models based on magnetic resonance (MR) images and convolutional neural network (CNN) models based on computed tomography (CT) images in predicting and staging liver fibrosis [12][13][14]. Other investigators have demonstrated in previous studies that SVM models based on digital pathology images may detect steatosis and assess the degree of liver fibrosis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ultrasound-based MLA is more accurate in detecting steatosis, hepatic fibrosis, and localized liver lesions [9][10][11]. Several studies have demonstrated the efficiency of support vector machine (SVM) models based on magnetic resonance (MR) images and convolutional neural network (CNN) models based on computed tomography (CT) images in predicting and staging liver fibrosis [12][13][14]. Other investigators have demonstrated in previous studies that SVM models based on digital pathology images may detect steatosis and assess the degree of liver fibrosis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Forty-two studies developed models addressing detection of steatosis, fibrosis, or cirrhosis based on clinical data, shear-wave elastography, CT or MRI scans, histopathology, or genetics. Of these, 27 studies developed models to detect, quantify, or predict steatosis, fibrosis, or cirrhosis[ 202 , 209 - 234 ]. Forlano et al [ 215 ] developed a ML-based model for quantification of steatosis, inflammation, ballooning, and fibrosis using biopsies from patients with NAFLD.…”
Section: Hepatobiliary Systemmentioning
confidence: 99%
“…Eventually, a total of 78 articles were included in the qualitative analysis, of which 17 were included in the quantitative analysis (15 studies on liver brosis and 2 studies on NAFLD). There were 11 studies integrating AI with imaging modalities, i.e., ultrasonography (21)(22)(23)(24)(25) , elastography (26,27) , computed tomography (CT) (28,29) and magnetic resonance imaging (MRI) (30,31) , to facilitate the diagnosis of liver brosis and NAFLD. The other 6 studies developed AI models using clinical and laboratory data, such as the presence of other underlying diseases or ascites, liver chemistry tests, and platelet and white blood cell counts, to predict liver brosis stages (32)(33)(34)(35)(36)(37) .…”
Section: Literature Searchmentioning
confidence: 99%
“…The other 6 studies developed AI models using clinical and laboratory data, such as the presence of other underlying diseases or ascites, liver chemistry tests, and platelet and white blood cell counts, to predict liver brosis stages (32)(33)(34)(35)(36)(37) . Regarding the types of AI, 6 studies used convolutional neural networks (CNNs) (21,23,(27)(28)(29)31) , 5 studies used arti cial neural networks (ANNs) (24,25,(34)(35)(36) , 5 studies used multiple AI models (22,26,32,33,37) and 1 study used a support vector machine (SVM) (30) . The study characteristics, sensitivity, speci city, prevalence, validation methods and other extracted data from the included studies are shown in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation